jtgg 2021
DOI: 10.20517/jtgg.2021.19
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetics in prostate cancer treatment

Abstract: Prostate cancer (PCa) is the most commonly diagnosed malignancy among men, and the progression of this disease results in fewer treatment options available to clinical patients. It highlights the vital necessity for discovering novel therapeutic approaches and expanding the current understanding of molecular mechanisms. Epigenetic alternations such as DNA methylation models and histone modifications have been associated as key drivers in the development and advancement of PCa. Several studies have been conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 131 publications
(142 reference statements)
0
10
0
Order By: Relevance
“…The gene-based analyses showed association between the genes H3C1, MBP, and MTG1 with PCa, and KLF5 with HRPCa. Modi cations to the H3 histone plays a key role in epigenetic regulation, and their relevance to PCa and treatment options have been reviewed elsewhere 52,53 . In this study, signi cant association of H3C1 to PCa suggests that differences in transcription may exist, and since the variant was only present in controls it may suggest a protective effect against PCa.…”
Section: Discussionmentioning
confidence: 99%
“…The gene-based analyses showed association between the genes H3C1, MBP, and MTG1 with PCa, and KLF5 with HRPCa. Modi cations to the H3 histone plays a key role in epigenetic regulation, and their relevance to PCa and treatment options have been reviewed elsewhere 52,53 . In this study, signi cant association of H3C1 to PCa suggests that differences in transcription may exist, and since the variant was only present in controls it may suggest a protective effect against PCa.…”
Section: Discussionmentioning
confidence: 99%
“…Some KDM1A inhibitors being investigated in clinical trials to treat cancers are: ORY-1001, ORY-2001, GSK-2879552, IMG7289, INCB059872 and CC-90011 (chemical structure shown in Figure 5 ) ( 106 ). Other histone demethylases like KDM3A, KDM4B/KDM4C, KDM6A/KDM6B have also been associated with regulating the transcriptional activity of AR ( 107 110 ). Moreover, inhibitors simultaneously targeting KDM4 and KDM1 family enzymes have been developed and shown to be effective in inducing apoptosis of PCa and colon cancer cell lines ( 111 ).…”
Section: Emerging Epigenetic Therapies For Advanced Prostate Cancermentioning
confidence: 99%
“…However, recently it was shown that it also exhibits a separate activation function when it binds to the promoter region of AR and plays a role in AR signaling. It also acts as a co-activator of AR in CRPC [reviewed by Jones et al ( 110 )]. Recently, a study found that inhibition of EZH2 enhanced enzalutamide activity and could potential overcome enzalutamide resistance in CRPC.…”
Section: Emerging Epigenetic Therapies For Advanced Prostate Cancermentioning
confidence: 99%
“…2,9−12 Overexpression of G9a has been reported in several cancer types, such as breast, 13,14 lung, 15,16 leukemia, 17 bladder, 18,19 colorectal, 20 and prostate. 21,22 G9a/GLP has also been implicated in diseases including sickle cell disease, 23 Prader−Willi syndrome, 24 and Alzheimer's disease. 25 In addition to G9a/GLP's wellestablished histone methyltransferase activity, studies have demonstrated that G9a/GLP has noncanonical oncogenic functions, such as methylating nonhistone proteins including HDAC1, DNMT1, and p53.…”
Section: ■ Introductionmentioning
confidence: 99%
“…G9a (also known as euchromatic histone-lysine N -methyltransferase 2 (EHMT2)) and G9a-like protein (GLP, also known as EHMT1) are lysine methyltransferases that catalyze mono- and dimethylation of histone H3 lysine 9 (H3K9), transcriptionally repressive chromatin marks, and nonhistone proteins. G9a and GLP, which share approximately 80% sequence homology in their catalytic SET domains, , play important roles in diverse cellular processes including cell development, differentiation, and hypoxia response. When atypically expressed, the G9a/GLP axis promotes cancer progression, survival, and metastasis. , Overexpression of G9a has been reported in several cancer types, such as breast, , lung, , leukemia, bladder, , colorectal, and prostate. , G9a/GLP has also been implicated in diseases including sickle cell disease, Prader–Willi syndrome, and Alzheimer’s disease . In addition to G9a/GLP’s well-established histone methyltransferase activity, studies have demonstrated that G9a/GLP has noncanonical oncogenic functions, such as methylating nonhistone proteins including HDAC1, DNMT1, and p53. Moreover, it has been shown that G9a/GLP have noncatalytic oncogenic activities by functioning as a coactivator independent of its catalytic domain. , For example, G9a positively regulates nuclear receptor gene expression by recruiting GRIP1, CARM1, and p300. ,, G9a is also recruited by Runx2 to downstream gene promoters to activate expression, , upregulates p21 via interaction with PCAF, and is a coactivator for a subset of p53 downstream genes, including pro-apoptotic Puma .…”
Section: Introductionmentioning
confidence: 99%